PENGUATAN PEMAHAMAN TENTANG WARISAN BUDAYA TAK BENDA INDONESIA BAGI MAHASISWA HEBEI INTERNATIONAL STUDIES UNIVERSITY MELALUI PELATIHAN TARI REYOG PONOROGO - Nursilah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract This community service aims to enhance the understanding of Hebei International Studies University (HISU) students regarding Indonesia’s intangible cultural heritage through Reyog Ponorogo dance training. The problem faced by the partner was the limited cultural understanding among HISU students studying Indonesian language, necessitating an innovative approach to introduce cultural elements into the language curriculum. The training was conducted both online and offline, involving 20 students, utilizing a teaching method that combined digital learning tools and direct instruction to ensure accessibility and engagement.The evaluation results demonstrated a significant increase in the students' cultural awareness, as evidenced by pre-test and post-test results, as well as their dance performance during campus orientation. Additionally, the students' active participation in the dance performance reflected a deeper understanding of Indonesian culture. Collaboration between Universitas Negeri Jakarta (UNJ) and HISU was formalized through an agreement, opening up opportunities for sustainable academic collaboration, including cultural exchange programs. This program not only introduced dance as a medium of cultural education but also laid the foundation for sustainable cross-country cultural exchanges through a successful hybrid learning model. The activity contributed to cultural diplomacy and strengthened cross-cultural relations between academic institutionsthe. Keywords: Intangible Cultural Heritage; Reyog Ponorogo Dance; Cross-Cultural Understanding; Cultural Enrichment Program; Promotion of Indonesian Culture. Abstrak Pengabdian ini bertujuan untuk memperkuat pemahaman mahasiswa Hebei International Studies University (HISU) tentang warisan budaya tak benda Indonesia melalui pelatihan Tari Reyog Ponorogo. Permasalahan yang dihadapi mitra adalah keterbatasan pemahaman budaya di kalangan mahasiswa HISU yang mempelajari bahasa Indonesia, sehingga diperlukan pendekatan inovatif untuk memperkenalkan elemen budaya dalam kurikulum bahasa. Pelatihan dilakukan secara daring dan luring, melibatkan 20 mahasiswa, dengan metode pengajaran yang mengombinasikan alat pembelajaran digital dan instruksi langsung untuk memastikan aksesibilitas dan keterlibatan. Hasil evaluasi menunjukkan peningkatan signifikan dalam kesadaran budaya mahasiswa, dibuktikan melalui pre-test dan post-test serta penampilan tari selama orientasi kampus. Selain itu, partisipasi aktif mahasiswa dalam pertunjukan tari menunjukkan pemahaman yang lebih mendalam tentang budaya Indonesia. Kerjasama antara Universitas Negeri Jakarta (UNJ) dan HISU diformalisasi melalui perjanjian yang membuka peluang kolaborasi akademik berkelanjutan, termasuk dalam program pertukaran budaya. Program ini tidak hanya memperkenalkan tari sebagai sarana pendidikan budaya, tetapi juga membangun landasan untuk keberlanjutan pertukaran budaya antar negara melalui model pembelajaran hybrid yang sukses. Kegiatan ini berkontribusi pada diplomasi budaya dan memperkuat hubungan lintas budaya di antara institusi akademis. Kata kunci: Warisan Budaya Takbenda; Tari Reyog Ponorogo; Pemahaman Lintas Budaya; Program Pengayaan Budaya; Promosi Budaya Indonesia.